Results of Intra-lesional Triamcinolone in the Treatment of Alopecia Areata - Wahab, MA (Journal of Bangladesh College of Physicians and Surgeons, 2007)
(J Bangladesh Coll Phys Surg 2006; 24 : 110-113)